THE DYNAMICS OF CRIMINAL PROCEDURE LAW ENFORCEMENT RELATED TO THE ELIMINATION OF THE INVESTIGATION STAGE IN THE DRAFT CRIMINAL PROCEDURE CODE - Rochmadi, Rochmadi; Nurdin, Boy (Ridwan Institute, 2024)
This study examines the impact of the elimination of the investigation stage in the Draft Criminal Procedure Code (RUU KUHAP) on the dynamics of criminal law enforcement in Indonesia. The study utilizes various data sources, including legislative texts, government regulations, judicial decisions, and academic literature related to the topic, in order to understand the legal foundation governing the issue. The author analyzed the data through a qualitative approach, employing comparative legal analysis to evaluate the implications of various legal provisions, exploring their effectiveness and relevance in law enforcement practice. Furthermore, the author engaged in thematic analysis to explore the broader impacts of these reforms on legal practice and the enforcement of the criminal law, assessing the effectiveness and relevant of the existing legal framework in light of the proposed reforms. The results demonstrate that the abolition of the investigator position in the draft criminal procedure code has significant implications for the criminal procedural law system in Indonesia, paving the way for further discussions on improving criminal procedure and enhancing the effectiveness of law enforcement. This research could contribute to refining the legal framework and operational practices in Indonesia to ensure a balance between effective crime control and the protection of civil liberties.